Web-Based Scholarship Management Information System Using Rapid Application Development (RAD) Model - Muhammad Rizki Hidayat; Irsan Jaelani; Mutiara Andayani Komara (RISTEC : Research in Information Systems and Technology, 2021)
The use of information systems in an organization has many advantages, just like the use of a website for institutions or companies is very helpful in conveying information, one of which is in administrative matters that can be applied using information system technology, namely for scholarship management. Scholarships can be interpreted as providing financial assistance to individuals, with the aim of being used for the continuity of the education taken. In the process of submission and approval in the selection of scholarship admissions that run in the field of student affairs at this time, it is still carried out manually both from the process of collecting files, selection to determining scholarship recipients is carried out manually by the head of the study program. Therefore, the field of Student Affairs at STT Wastukancana Purwakarta, requires an information system that can help the process of applying for and approving scholarships digitally carried out by students of each study program coordinated by the student affairs field. The system development method used is the Rapid Application Development (RAD) model consisting of the Requirements Planning, RAD Workshop Design, and Implementation stages. The results of this study produce a scholarship management information system that can solve problems in the scholarship admission selection process by being able to do it digitally from the process of informing the existence of scholarship opportunities, submission, selection to determining scholarship recipients.